Optimization of surgical treatment of uterine myoma in women with obesity and the metabolic syndrome - N.V. Kosei; T.F. Tatarchuk; K.D. Plaksiieva; Y.O. Dubossarska; H.A. Tokar; O.S. Kozlov (Репродуктивная эндокринология, 2023)
Objectives: to evaluate the benefits of delayed conservative myomectomy with the aim of reducing body weight and correcting hematological and metabolic parameters against the background of the use of gonadotropin-releasing hormone (GnRH) agonists and a combination of myo-inositol and D-chiro-inositol (Inofolic combi) in obese patients with metabolic syndrome by comparing this technique with immediate surgery. Materials and methods. The study included 72 patients with uterine fibroids and obesity who required conservative myomectomy. Patients were offered to postpone surgical intervention in order to correct body weight, metabolic and hematological indicators. As a preoperative preparation, patients were recommended to use GnRH agonists (goserelin), inositols, and iron preparations for anemia. Patients were divided into 2 groups: the first group (n = 31) followed all these recommendations, the second group (n = 41) refused to follow the recommendations and postponed surgical treatment. Group 1 underwent surgical treatment 3 months after the start of treatment, group 2 – after the initial consultation. Results. Patients of the first group lost an average of 7.3 ± 1.4 kg of body weight during preoperative preparation, their hemoglobin level increased by an average of 21.78%, and the volume of the largest myomatous node decreased by an average of 21.82%. The duration of the operation was significantly shorter in group 1 (75 ± 3.84 min) than in group 2 (118 ± 5.33 min). Laparotomy in the first group was not performed in any patient, in the second group it was performed in 9 patients (21.95%) (p < 0.05). There was a decrease in the severity of postoperative pain in group 1, (3.4 В± 1.25 points on the visual analog scale), which was significantly lower than in group 2 (5.1 В± 3.4 points). Conclusions. Body weight reduction against the background of the use of GnRH agonists (goserelin) and inositols (Inofolic combi) due to the improvement of the technical conditions of the operation, metabolic and hematological indicators allow to reduce the duration of surgical intervention and the frequency of laparotomies in patients with uterine fibroids against the background of obesity and metabolic syndrome.